Lista y referencias de los crustáceos anfípodos (Amphipoda: Gammaridea) del Atlántico occidental tropical - Ortíz, Manuel; Martín, Alberto; Díaz, Yusbelly J. (Revista de Biología Tropical, 2007)
The published records of Amphipoda Gammaridea of the tropical western Atlantic region were reviewed and compiled in a checklist. A total of 478 species is recorded (52 families, 199 genera). This adds 20 families and 253 species to the last published list. The families are Ampeliscidae, Amphilochidae, Amphitoidae, Anamixidae, Aoridae, Argissidae, Aristiidae, Bateidae, Biancolinidae, Bogidiellidae, Cheluridae, Colomastigidae, Corophiidae, Cyphocarididae, Cyproideidae, Dexaminidae, Endevouridae, Epimeriidae, Eusiridae, Gammaridae, Hadziidae, Haustoriidae, Hyalellidae, Hyalidae, Hyperiopsidae, Iphimediidae, Isaeidae, Ischyroceridae, Leucothoidae, Liljeborgiidae, Lysianassidae, Megaluropidae, Melitidae, Melphidippidae, Ochlesidae, Oedicerotidae, Pardaliscidae, Phliantidae, Phoxocephalidae, Platyischnopidae, Pleustidae, Podoceridae, Pontoporeiidae, Scopelocheiridae, Sebidae, Stegocephalidae, Stenothoidae, Synopiidae, Talitridae, Uristidae, and Vitjazianidae.